Law Enforcement of Symbolic Violence against Women in the Context of the Domestic Violence Eradication Law - Maulida, Irma; Faturachman, Dadan Taufik; Harliyanto, Rois; Sutrisno, Anom; Ika Putri, Dessy; Azizah, Nur Alma; Noupel, Muhamad (Ann Publisher, 2025)
Background, The notion of domestic violence, frequently rationalized by the general populace, predominantly manifests as physical aggression. However, the inclination to prioritize physical and interpersonal dimensions of violence obscures the recognition of non-physical forms, leading to the conclusion that violence is inherently subjective. Several cases of symbolic violence often appear in society, one of which is about expressing a wife's feelings of sadness and disappointment for accepting her husband's betrayal in a marriage relationship that has been lived for years even though it does not physically hurt, but this violence can occur because of masculine dominance. This dominant position of men contributes to symbolic violence as a result of patriarchal culture. Aim, This research aims to identify the factors contributing to symbolic violence against women within households that persist in a patriarchal culture and to examine law enforcement related to symbolic violence against women in the context of the Law on the Elimination of Domestic Violence. Methods, This research employs a normative juridical approach, focusing on the implementation of laws against symbolic violence towards women as examined through the Law on the Elimination of Domestic Violence. Data gathering methods included in this study include literature analysis, interviews, and observations. Results, Numerous victims of domestic violence remain hesitant or afraid to report the abuse they have endured. This is affected by multiple factors, including the stigma associated with domestic violence, economic reliance on the abuser, and the inadequate response of law enforcement officials. Conclusions, By combining effective prevention and intervention approaches, this effort is believed to not only reduce cases of symbolic violence but also improve family relationships, create a more harmonious society, and support the comprehensive elimination of domestic violence. Implication, The findings of this study indicate that law enforcement on the Law on the Elimination of Domestic Violence in Cirebon necessitates more enhancement and oversight, particularly with symbolic violence against women inside the domestic context.